Increasing situational awareness through nowcasting of the reproduction number - Bizzotto, Andrea; Guzzetta, Giorgio; Marziano, Valentina; Del Manso, Martina; Mateo Urdiales, Alberto; Petrone, Daniele; Cannone, Andrea; Sacco, Chiara; Poletti, Piero; Manica, Mattia; Zardini, Agnese; Trentini, Filippo; et al. (Frontiers in Public Health, 2024)
Background The time-varying reproduction number R is a critical variable for situational awareness during infectious disease outbreaks; however, delays between infection and reporting of cases hinder its accurate estimation in real-time. A number of nowcasting methods, leveraging available information on data consolidation delays, have been proposed to mitigate this problem. Methods In this work, we retrospectively validate the use of a nowcasting algorithm during 18 months of the COVID-19 pandemic in Italy by quantitatively assessing its performance against standard methods for the estimation of R. Results Nowcasting significantly reduced the median lag in the estimation of R from 13 to 8 days, while concurrently enhancing accuracy. Furthermore, it allowed the detection of periods of epidemic growth with a lead of between 6 and 23 days. Conclusions Nowcasting augments epidemic awareness, empowering better informed public health responses.